Hubungan Pengetahuan dan Sikap Suami terhadap Pemanfaatan Buku KIA di Kabupaten Aceh Barat - Evi Zahara (Indonesian Journal for Health Sciences, 2023)
The Midwiferyternal and Child Health (KIA) books can improve the quality of maternal and child health services as well as nutrition, so one of the national development goals, namely reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), can be achieved. However, the husband does not take advantage of the material and information contained in the MCH handbook and considers it only needs to be known by the midwife and wife. This research aims to prove the relationship between the husband's knowledge and attitude towards using MCH books in Aceh Barat District. This research is an analytic survey with a cross-sectional approach using Chi-Square statistical test. The population in this study were the husbands of pregnant women in the third trimester in West Aceh Regency as many This research aims carried out using two-stage cluster sampling. They have obtained as many as 256 people. The results of the analysis showed that there was a relationship between husband's knowledge of the use of MCH books in Aceh Barat District (p-value 0.02 sig_α = 0.05), there was no relationship between husbands' attitudes towards the use of MCH books in Aceh Barat District (p-value 0.059 sig_α = 0.05). So the two stages suggest that midwives can always inform and evaluate mothers and husbands about the use of MCH books.